Mismatches of threat status and actual extinctions in Quaternary reef corals - Raja, Nussaïbah Begum; Lauchstedt, Andreas; Pandolfi, John M.; Kim, Sun W.; Budd, Ann F.; Kießling, Wolfgang (GSA 2020 Connects Online, 2020)
Species traits and spatial distributions influence the extinction risk of species as a result of abiotic and biotic change. We performed a comparative assessment of the relationship between traits and extinction risk of reef corals in the modern oceans against Plio-Pleistocene reef corals. We chose the Plio-Pleistocene as most of the corals during this time are still present today and their traits are thus comparable to those of modern corals. As such, the regional extinctions of reef corals during this time, attributed to climate change, may shed light on which traits contribute to the resilience or vulnerability of reef building corals in the face of contemporary ocean warming. We applied predictive modelling using two morphological and two distributional traits of 585 extant reef coral species together with data on extinction risk as reported by the International Union for Conservation of Nature (IUCN). This model was then validated against the fossil corals. Although our model performed well in the prediction of the extinction risk of modern corals (82% match), the match between our modelled extinction risk and observed extinction during the Plio-Pleistocene was not better than random. This suggests that either 1) the IUCN status for reef corals may not reflect true extinction risk, or 2) the drivers of extinction during the Plio-Pleistocene may be considerably different from the conditions currently observed in the oceans. This underlines the need to incorporate fossil data when assessing the vulnerability of extant species to climate chang